2021
DOI: 10.1136/bmjgast-2021-000603
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the coronavirus infectious disease (COVID-19) pandemic on the provision of inflammatory bowel disease (IBD) antenatal care and outcomes of pregnancies in women with IBD

Abstract: BackgroundThe impact of COVID-19 on pregnant inflammatory bowel disease (IBD) patients is currently unknown. Reconfiguration of services during the pandemic may negatively affect medical and obstetric care. We aimed to examine the impacts on IBD antenatal care and pregnancy outcomes.MethodsRetrospective data were recorded in consecutive patients attending for IBD antenatal care including outpatient appointments, infusion unit visits and advice line encounters.ResultsWe included 244 pregnant women with IBD, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The majority of studies reported findings from a single hospital site or group of facilities relating to specific and highly variable changes in protocols made during the pandemic [ 13 , [23] , [24] , [25] , [26] , [37] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. This ranged from the institution of new telehealth services [ 29 , 33 , 35 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ], altered hospital admission and discharge protocols [ 27 , 30 , [48] , [49] , [50] ], variance in anaesthetic management [ 27 , 36 , 51 , 52 ], and harmonisation of regional antenatal screening services [ 32 , 53 , 54 ]. Only 14 of the 56 papers reported data from low- or middle-income (LMIC) countries according to World Bank classification [ 13 , 28 , 37 , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies reported findings from a single hospital site or group of facilities relating to specific and highly variable changes in protocols made during the pandemic [ 13 , [23] , [24] , [25] , [26] , [37] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. This ranged from the institution of new telehealth services [ 29 , 33 , 35 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ], altered hospital admission and discharge protocols [ 27 , 30 , [48] , [49] , [50] ], variance in anaesthetic management [ 27 , 36 , 51 , 52 ], and harmonisation of regional antenatal screening services [ 32 , 53 , 54 ]. Only 14 of the 56 papers reported data from low- or middle-income (LMIC) countries according to World Bank classification [ 13 , 28 , 37 , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies [ 13 , 26 , 28 , 29 , 33 , [35] , [36] , [37] , 40 , 42 , [44] , [45] , [46] , [47] , 50 , [56] , [57] , [58] , 60 , [65] , [66] , [67] , [68] , [69] , [70] ] reported on antenatal clinic attendance during the pandemic using a variety of metrics. In several settings, no alteration was made to the standard antenatal care protocol, but decreased antenatal clinic attendance was reported in the majority of studies; in high income settings a decline in face to face contacts was offset by an increase in remote or virtual clinic appointments and the nature but not the number of the appointments varied [ 26 , 29 , 35 , 40 , [42] , [43] , [44] , [45] , 47 , 66 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, the majority of health care encounters occurred by telephone (68.2%, compared to 3% prior to the pandemic). There was no increase in the number of IBD-related questions to their advice-line, compared to before the pandemic ( 34 ). Preliminary results from a Canadian survey of pregnant people with IBD also found no confirmed cases of COVID-19, although 8 of 29 participants had symptoms suspicious for COVID-19 ( 35 ).…”
Section: Covid-19 and Pregnant People With Ibdmentioning
confidence: 89%
“…Very few studies have assessed the impact of COVID-19 on pregnant people with IBD. A registry of IBD prenatal care provided in 13 British hospitals found no confirmed cases of COVID-19 among 244 pregnant people with IBD, and a very low rate of negative pregnancy outcomes ( 34 ). In that study, the majority of health care encounters occurred by telephone (68.2%, compared to 3% prior to the pandemic).…”
Section: Covid-19 and Pregnant People With Ibdmentioning
confidence: 99%